Experimental investigation of the icing scaling test method for a rotating cone. (July 2019) - Zhang, Fei; Zhang, Lifen; Li, Yundan; Liu, Zhenxia; Zhu, Pengfei
One of the reliable methods of studying engine icing is to carry out testing in an icing wind tunnel. Due to the operational limitations of test facility, model-size scaling is adopted. An icing scaling test method for the rotating cone is established based on the dimensional analysis coupled with similarity theory and evaluated by considering the rotating effect. Similarity parameters are determined in the following five aspects: flow field similarity, droplet trajectory similarity, water catch similarity, heat balance similarity, and rotating characteristics similarity. Experimental icing tests have been performed at rime and glaze ice conditions to evaluate the scaling method in a closed-loop icing wind tunnel. Results show that the maximum error between the reference and scale ice shapes occurs at the stagnant point. On the areas apart from this, there is a significantly smaller error. Hence, the scaling test method is proven to be effective and reliable and can provide a theoretical basis for parameter selection of the ice wind tunnel tests.